The Effect of Maggot Black Soldier Fly (Hermetia illucens) on Liquid Organic Fertilizer Production - Dewi, Desak Made Devika Ratna; Farista, Baiq; Virgota, Arben; Kamali, Siti Raudhatul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The problem of organic waste in the environment can be overcome by using organic waste bioconversion technology using maggots. This technology produces a by-product in the form of leachate that can be used as Liquid Organic Fertilizer (POC). On the other hand, research on the effect of maggots on the quality and quantity of POC produced has not been widely studied. This study aims to 1). determine the quality of POC based on the concentration of N, P and K; 2). Determine the quantity of POC based on the volume of POC. The method used is an experimental method with the treatment of organic waste conversion using maggots (M1) and without maggots (M0). Each treatment was repeated 4 times. Data were analyzed using the t-independent test with the help of the SPSS version 22 application. The time of this research was carried out in May 2024 - July 2024. The location of the research was carried out at the Lingsar Regional Integrated Waste Processing Site (TPSTR) and the Soil Chemistry Laboratory of the University of Mataram. The results of this study indicate that the quality of liquid organic fertilizer (POC) in M1 is better than M0. The content of N (nitrogen), P (phosphorus) and K (potassium) in M1 were 0.14%, 0.11%, and 0.17% respectively, while M0 was 0.11%, 0.06%, and 0.09% respectively. The t-independent test showed that there was a significant difference between M0 and M1. The content of N, P and K in this study was still below the standard quality values ​​based on the Decree of the Minister of Agriculture of the Republic of Indonesia Number 261/KPTS/SR.310/M/4/2019 concerning Minimum Technical Requirements for Organic Fertilizers, Biological Fertilizers and Soil Improvers.